2015
DOI: 10.3349/ymj.2015.56.5.1449
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Vitamin C Promotes Regression of Multiple Pulmonary Metastases Originating from Hepatocellular Carcinoma

Abstract: We report a case of regression of multiple pulmonary metastases, which originated from hepatocellular carcinoma after treatment with intravenous administration of high-dose vitamin C. A 74-year-old woman presented to the clinic for her cancer-related symptoms such as general weakness and anorexia. After undergoing initial transarterial chemoembolization (TACE), local recurrence with multiple pulmonary metastases was found. She refused further conventional therapy, including sorafenib tosylate (Nexavar). She di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 21 publications
(21 reference statements)
0
9
0
Order By: Relevance
“…Some of these results include reversal of pulmonary metastases from RCC and from hepatocellular carcinoma. 26 , 27 …”
Section: Discussionmentioning
confidence: 99%
“…Some of these results include reversal of pulmonary metastases from RCC and from hepatocellular carcinoma. 26 , 27 …”
Section: Discussionmentioning
confidence: 99%
“…She did receive high doses of vitamin C (70 g), which were administered into a peripheral vein twice a week for 10 months, and multiple pulmonary metastases were observed to have completely regressed. She then underwent subsequent TACE, resulting in remission of her primary hepatocellular carcinoma [ 215 ].…”
Section: Vitamin Cmentioning
confidence: 99%
“…Pharmacokinetic studies indicate that high ascorbate concentrations associated with these phenomena may be achievable in vivo, provided ascorbate is administered intravenously [24][25][26]. Many case studies demonstrated the effectiveness of intravenous vitamin C, with various degrees of success [27][28][29][30][31][32][33]. Clinically published IVC case studies report efficacy against a variety of cancers in humans, including pancreatic cancer, bone metastases accompanying breast cancer, non-Hodgkin's lymphoma, liver carcinoma, colon carcinoma, and ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%